2021
DOI: 10.1007/s00268-021-06266-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult Benign, Non‐Iatrogenic Bronchoesophageal Fistulae: Systematic Review and Descriptive Analysis of Individual Patient Data

Abstract: Background Adult, benign, non-iatrogenic bronchoesophageal fistula (BEF) is a rare condition, which is occasionally described in single case reports. Therefore, little is known about its possible causes, presentation and management. Methods A systematic search of the literature in MEDLINE, PubMed Central and EMBASE databases between 1990 and 2020 was carried out to identify all cases of BEF. The initial database search identified 19,452 articles, of which 183 (251 individual patient cases) were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…13 Mammana et al reported that among 25 endoscopically-treated patients with bronchoesophageal fistula, 4 patients received combined endoscopic treatments, and the most common endoscopic tools were clips, stents, glue, and septal occluders. 14 Therefore, the combination of ESD-based suture and medical adhesive was proposed and implemented, in this case. Esophageal ESD around the fistulous orifice was intended to provide a larger mucosal defect for the subsequent endoscopic nylon loop suture.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mammana et al reported that among 25 endoscopically-treated patients with bronchoesophageal fistula, 4 patients received combined endoscopic treatments, and the most common endoscopic tools were clips, stents, glue, and septal occluders. 14 Therefore, the combination of ESD-based suture and medical adhesive was proposed and implemented, in this case. Esophageal ESD around the fistulous orifice was intended to provide a larger mucosal defect for the subsequent endoscopic nylon loop suture.…”
Section: Discussionmentioning
confidence: 99%
“…The median time from symptom development to diagnosis of malignant ADFs has been reported between 3 days to 7 months with a range of 0–58 months ( 4 , 6 , 11 ). The most common symptoms include coughing after swallowing (“Ono’s sign”) in 20–100% of patients, dysphagia in 8–100%, purulent tracheobronchitis in 15–100%, pneumonia in 5–95%, chronic cough in 20–81%, dyspnea in 18–69%, cachexia and malnutrition in 18–60%, aspiration in 23–46%, fever in 21–27%, chest pain in 5–23%, respiratory failure requiring mechanical ventilation in 6–15%, and hemoptysis or hematemesis in 2–3% ( 4 , 6 , 12 - 17 ).…”
Section: Presentationmentioning
confidence: 99%
“…Once an ADF is suspected, the first diagnostic study is typically an esophagram as it is easy to obtain with a sensitivity estimated between 70–97% ( 17 , 18 ). Oral barium sulfate is the contrast of choice over Gastrografin because aspiration of Gastrografin has been associated with fatal pneumonitis and pulmonary edema due to the iodine content as well as the hyperosmolarity of the contrast solution, respectively ( 19 ).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations